2018
DOI: 10.1038/s41467-018-05745-w
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-resident RIG-I senses viral replication inducing antiviral immunity

Abstract: The nucleus represents a cellular compartment where the discrimination of self from non-self nucleic acids is vital. While emerging evidence establishes a nuclear non-self DNA sensing paradigm, the nuclear sensing of non-self RNA, such as that from nuclear-replicating RNA viruses, remains unexplored. Here, we report the identification of nuclear-resident RIG-I actively involved in nuclear viral RNA sensing. The nuclear RIG-I, along with its cytoplasmic counterpart, senses influenza A virus (IAV) nuclear replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 62 publications
(86 reference statements)
3
72
0
1
Order By: Relevance
“…RNA sensors like the RIG-I-like sensors or TLRs were thought to be absent there, and therefore replication inside the nucleus may have been an alternative solution to avoid innate immune recognition of viral RNA intermediates during replication. However, recent data indicated that RIG-I can be active in the nucleus against influenza RNA [51]. The viral genome, packaged in nucleocapsid proteins and bearing a panhandle-and 5′-triphosphate structure is recognized by RIG-I, presumably in the cytosol while on its way to the nucleus, or when being incorporated into new virus particles [52][53][54].…”
Section: Attack Of the Replication Organelles By The Innate Immune Symentioning
confidence: 99%
“…RNA sensors like the RIG-I-like sensors or TLRs were thought to be absent there, and therefore replication inside the nucleus may have been an alternative solution to avoid innate immune recognition of viral RNA intermediates during replication. However, recent data indicated that RIG-I can be active in the nucleus against influenza RNA [51]. The viral genome, packaged in nucleocapsid proteins and bearing a panhandle-and 5′-triphosphate structure is recognized by RIG-I, presumably in the cytosol while on its way to the nucleus, or when being incorporated into new virus particles [52][53][54].…”
Section: Attack Of the Replication Organelles By The Innate Immune Symentioning
confidence: 99%
“…The relative quantitation of vRNA and cRNA in the cRNA stabilization assay was determined by a strand-specific real-time RT-PCR as previously described [23,27,28]. Briefly, total RNA (350 ng) was reverse-transcribed at 60 • C for 1 h in a 20-µL reaction containing 10 pmol 5 -tagged RT primer, 0.5 mM dNTP mix, 1 × first-strand buffer, 5 mM DTT, 50 U RNaseOUT, 200 U SuperScript III reverse transcriptase (Invitrogen, Carlsbad, CA, USA), and 32.5% saturated trehalose (Sigma).…”
Section: Strand-specific Real-time Rt-pcrmentioning
confidence: 99%
“…To avoid the possibility that the RNA extraction procedure was inefficient in extracting viral immunostimulatory RNA generated during NP deprivation or disrupted the native RNA structures of these RNAs, we determined in situ RIG-I activation during RNP reconstitution in the presence or absence of NP. Since IAV RNA synthesis takes place in the nucleus, supplementation of reporter cells with a nuclear-localized RIG-I (NLS-RIG-I) provided a more sensitive measurement of IFN-␤ promoter activation in response to RNP reconstitution (6). Furthermore, this may also shed light on the specialized sensing by nuclear RIG-I of a subset of unknown viral RNAs in the nucleus.…”
Section: Dmentioning
confidence: 99%
“…For over a decade, it has been clear that RIG-I plays an indispensable role in type I IFN induction by IAV (2,3). Recent identification of RIG-I in the nuclear milieu sheds further light on its spatiotemporal detection of IAV replication (6). In contrast, the physiological RIG-I agonists produced from IAV remain underexplored.…”
mentioning
confidence: 99%